Novel hardware implementation for generating message authentication codes - Michail, Harris; Kakarountas, Athanasios P.; Fotopoulou, Eleni; Goutis, G. E. (My University, 2005)
HMAC mechanism rely his security in the underlying hash function. This mechanism is used for authentication codes between two parties that share a secret key in order to authenticate information transmitted between these parties. Currently used HMAC implementations utilize MD-5 or SHA-1 hash functions that both have now been proved to be vulnerable. This affects the security level provided by the HMAC mechanism and thus in the near future a more secure hash function will be used. One of them is the SHA-256 hash function which is used the HMAC implementation presented in this paper. The proposed hardware implementation, invokes a partially unrolled implementation for the underlying hash function leading to a high-throughput and low-power implementation for the whole HMAC construction.
Keywords: Computer networks; Public key cryptography; Security